2013
DOI: 10.7314/apjcp.2013.14.2.835
|View full text |Cite
|
Sign up to set email alerts
|

miR-19a Promotes Cell Growth and Tumorigenesis through Targeting SOCS1 in Gastric Cancer

Abstract: Accumulating evidence has shown that microRNAs are involved in cancer development and progression. However, it remains unknown about the potential role of miR-19a in the pathogenesis of gastric cancer. Here, we report that suppressor of cytokine signaling 1 (SOCS1) is a novel target of miR-19a in gastric cancer cells and that miR-19a expression is inversely correlated with SOCS1 expression in gastric cancer cells and a subset of gastric cancer tissues. Ectopic expression of miR-19a dramatically promoted prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 25 publications
5
33
0
Order By: Relevance
“…Gregory reported that miRNAs, such as smiR-200 family and miR-205, act as key modulators of EMT and enforcers of the epithelial phenotype targeting ZEB1 and SIP1 [26]. Dong et al demonstrated miR-194 directly targets BMI-1, and reverses EMT phenotype in endometrial cancer cells [27]. To the best of our knowledge, however, the definitive association of miR-19a with EMT of GC has not been reported, only given the evidences showing that the oncogenic effect of miR-19a was mediated by repression of SOCS1, MXD1 [6,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gregory reported that miRNAs, such as smiR-200 family and miR-205, act as key modulators of EMT and enforcers of the epithelial phenotype targeting ZEB1 and SIP1 [26]. Dong et al demonstrated miR-194 directly targets BMI-1, and reverses EMT phenotype in endometrial cancer cells [27]. To the best of our knowledge, however, the definitive association of miR-19a with EMT of GC has not been reported, only given the evidences showing that the oncogenic effect of miR-19a was mediated by repression of SOCS1, MXD1 [6,27].…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al demonstrated miR-194 directly targets BMI-1, and reverses EMT phenotype in endometrial cancer cells [27]. To the best of our knowledge, however, the definitive association of miR-19a with EMT of GC has not been reported, only given the evidences showing that the oncogenic effect of miR-19a was mediated by repression of SOCS1, MXD1 [6,27]. For the first time, we found that up-regulation of miR-19a level is able to induce EMT in GC cells, evidenced by epithelial like morphology, increased expression of E-cadherin and decreased expression of vimentin.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that miRNAs have crucial functions in specific cellular processes such as differentiation, morphogenesis, and tumorigenesis. In human cancer, miRNAs can function as oncogenes (Qin et al, 2013) or tumor suppressor genes (Hagman et al, 2013) during tumorigenesis. Gene expression profiling studies have demonstrated that miRNA expression is an excellent biomarker associated with specific tumor subtypes and clinical outcomes (Dieckmann et al, 2012;Takahashi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…miR-19a functions as an oncogenic miRNA in gastric cancer by repressing the expression of tumor suppressor gene SOCS1 (Suppressor of cytokine signaling 1) [17]. miR-296-5p increased cell proliferation in gastric cancer through repression of caudal-related homeobox 1 [18].…”
Section: The Involvement Of Mirnas As Oncogenes or Tumor Suppressors mentioning
confidence: 99%